Path Analysis on the Biological and Social-Economic Determinants of Anemia in Pregnant Mothers in Bantul, Yogyakarta - Reso, Mulya Cunda Ratu; Dewi, Yulia Lanti Ratna; Budihastuti, Uki Retno (Journal of Maternal and Child Health, 2019)
Background: Anemia in pregnant women is one of the public health problems that is still considered as a serious problem. The most important things in handling cases of anemia in pregnant women is to pay attention to biological and socio-economic factors in pregnant women. This study aimed to determine the effect of biological and socio-economic factors on the incidence of anemia among pregnant women. Subjects and Method: This was a cross sectional study conducted in Bambanglipuro community health center, Bantul, Yogyakarta, from March to April 2019. A sample of 200 pregnant women was selected by fixed disease sampling. The dependent variable was anemia. The independent variables were age, gestational age, parity, birth spacing, education, income, adherence to iron tablet consumption, contraceptive use before pregnancy, dietary pattern, and body mass index (BMI). The data were collected by questionnaire and analyzed by path analysis. Results: The risk of anemia in pregnant women was directly and positively affected by education <Senior high school (b=1.92; 95% CI=0.67 to 3.17; p=0.003), age <20 or ?35 years old (b=1.27; 95% CI= 0.09 to 2.46; p=0.036), parity ?3 times (b=1.57; 95% CI= 0.42 to 2.72; p=0.007), birth spacing <2 years (b=2.58; 95% CI= 1.23 to 3.93; p<0.001), gestational age (II and III trimesters) (b=2.07; 95% CI=0.69 to 3.45; p=0.003), BMI <18.5 (b=3.21; 95% CI=1.98 to 4.44; p<0.001), and irregular iron tablet consumption (b=1.46; 95% CI=0.31 to 2.62; p=0.013). It was indirectly affected by education, history of contraceptive use, dietary pattern, and family income. Conclusion: The risk of anemia in pregnant women is directly and positively affected by education <Senior high school, age <20 or ?35 years old, parity ?3 times, birth spacing <2 years, gestational age (II and III trimesters), BMI <18.5, and irregular iron tablet consumption. It is indirectly affected by education, history of contraceptive use, dietary pattern, and family income. Keywords: anemia, iron tablet consumption, dietary pattern, path analysis